Scope of the directed dihydroxylation: application to cyclic homoallylic alcohols and trihaloacetamides. - Donohoe, T; Mitchell, L; Waring, M; Helliwell, M; Bell, A; Newcombe, N (2003)
The synthesis and directed dihydroxylation of a range of cyclic alkenes was investigated. Both homoallylic alcohols and homoallylic trihaloacetamides were found to be efficient directing groups, giving rise to good to excellent levels of remote asymmetric induction with OsO4-TMEDA. Interestingly, in all cases examined, trifluoroacetamides were found to be superior to trichloroacetamides as directing groups and an argument is presented which rationalises this observation.